"Kategorija istrijanstva" - između "centra" i "periferije" - Medica, Karmen (Annales. Series historia et sociologia, 1998)
Istra, benig a unitary geographical area, is nowdays divided into three parts belonging to three different national states (Croatia, Slovenia, Italy). The two state borders certainly represent, in the relativity restriced area, an obstacle for a normal circular flow of people, raw materials, goods and capital. Both natural and traditional bonds between the inhabitants of the Istran peninsula are overburdened. Bordelands with the complex ethnic structure, as is the case with the Istran peninsula, give rise to some particular ethnic identities influencing each other. The recognition of the Istran ethnolinguistic heterogeneity and its transformation into a cultural value has helped in the formation of a distinct identity, manifested through the category of Istranity.
Keywords: Istra; Istria; nacionalna identiteta; narodnostno vprašanje